Degradability enhancement of poly(lactic acid) by stearate-Zn3Al LDH nanolayers - Eili, Mahboobeh; Shameli, Kamyar; Ibrahim, Nor Azowa; Wan Yunus, Wan Md. Zin (MDPI, 2012)
Recent environmental problems and societal concerns associated with the disposal of petroleum based plastics throughout the world have triggered renewed efforts to develop new biodegradable products compatible with our environment. This article describes the preparation, characterization and biodegradation study of poly(lactic acid)/layered double hydroxide (PLA/LDH) nanocomposites from PLA and stearate-Zn3Al LDH. A solution casting method was used to prepare PLA/stearate-Zn3Al LDH nanocomposites. The anionic clay Zn3Al LDH was firstly prepared by co-precipitation method from a nitrate salt solution at pH 7.0 and then modified by stearate anions through an ion exchange reaction. This modification increased the basal spacing of the synthetic clay from 8.83 Å to 40.10 Å. The morphology and properties of the prepared PLA/stearate-Zn3Al LDH nanocomposites were studied by X-ray diffraction (XRD), transmission electron microscope (TEM), scanning electron microscope (SEM), thermogravimetric analysis (TGA), tensile tests as well as biodegradation studies. From the XRD analysis and TEM observation, the stearate-Zn3Al LDH lost its ordered stacking-structure and was greatly exfoliated in the PLA matrix. Tensile test results of PLA/stearate-Zn3Al LDH nanocomposites showed that the presence of around 1.0–3.0 wt % of the stearate-Zn3Al LDH in the PLA drastically improved its elongation at break. The biodegradation studies demonstrated a significant biodegradation rate improvement of PLA in the presence of stearate-Zn3Al LDH nanolayers. This effect can be caused by the catalytic role of the stearate groups in the biodegradation mechanism leading to much faster disintegration of nanocomposites than pure PLA.